2021
DOI: 10.1002/celc.202100217
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum and Phosphorous Dual‐Doped, Transition‐Metal‐Based, Free‐Standing Electrode for Overall Water Splitting

Abstract: Water splitting using earth-abundant, low-cost, highly efficient, transition-metal-based electrocatalysts with high activity and stability is inevitable for sustainable energy development. Herein, a molybdenum (Mo) and phosphorous (P) co-doped highly efficient and durable electrocatalyst is grown on nickel foam (P-NiCo 2 O 4 /CoMoO 4 /NF, for simplicity G-3) for hydrogen and oxygen evolution reactions (HER and OER, respectively). The dual doping of Mo and P prompts the formation of nanosheet array structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous studies indicate that these two main splitorbit peaks are indicative of the hexavalent Mo 6+ oxidation state. 9,43,44 The S 2p spectrum resolution is high (Fig. 4d), showing two signals at 163.1 eV and 164.7 eV, corresponding to S 2p 3/2 and S 2p 1/2 states, 34,[45][46][47] and the peak at 169.8 eV is correlated with SO 4 2− , which is caused by surface oxidation.…”
Section: Crystengcomm Papermentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies indicate that these two main splitorbit peaks are indicative of the hexavalent Mo 6+ oxidation state. 9,43,44 The S 2p spectrum resolution is high (Fig. 4d), showing two signals at 163.1 eV and 164.7 eV, corresponding to S 2p 3/2 and S 2p 1/2 states, 34,[45][46][47] and the peak at 169.8 eV is correlated with SO 4 2− , which is caused by surface oxidation.…”
Section: Crystengcomm Papermentioning
confidence: 97%
“…where "M" represents the metal ions, and the theoretical values of the Volmer, Heyrovsky and Tafel reactions are 120, 40, and 30 mV dec −1 , respectively. 9 The reaction may follow one of the two reaction pathways i.e., the Volmer reaction can be followed by either the Heyrovsky or Tafel reaction. If Volmer adsorption process represents the rate-limiting step, the Tafel slope should be approximately120 mV dec −1 .…”
Section: Crystengcomm Papermentioning
confidence: 99%
See 1 more Smart Citation
“…[80][81][82][83][84][85] Moreover, DFT calculations demonstrated that an effective "H delivery" transport channel existed in MoP, indicating its potential for HER. [86,87] Using NENU-5 as the precursor followed by carbonization, FeCl 3 etching and phosphorization by (NH 4 ) 2 HPO 4 as a P source, Li et al synthesized P-doped carbon encapsulated MoP (MoP@PC) for HER (Figure 7a). [88] Owing to the synergistic effect of P dopant, the high catalytic activity of MoP nanocrystal and the high porous carbon, the MoP@PC exhibited an onset potential of 97 mV for HER (Figure 7b), a small Tafel slope of 59.3 mV dec −1 , and good long-term durability for more than 1000 cycle (Figure 7c).…”
Section: Molybdenum Phosphidesmentioning
confidence: 99%
“…[ 80–85 ] Moreover, DFT calculations demonstrated that an effective “H delivery” transport channel existed in MoP, indicating its potential for HER. [ 86,87 ]…”
Section: Molybdenum Phosphidesmentioning
confidence: 99%